Ocular toxoplasmosis I: parasitology, epidemiology and public health. (11th July 2012) - Furtado, João M; Winthrop, Kevin L; Butler, Nicholas J; Smith, Justine R
Abstract : Ocular toxoplasmosis results from retinal infection with the protozoan, Toxoplasma gondii. This parasite, which exists as multiple clonal subpopulations and in three stages, is capable of replication in any nucleated cell of its primary feline or multiple paratenic hosts. Human seroprevalence of toxoplasmosis is high across the globe, but with geographic variation. While prevalence of ocular toxoplasmosis is not well documented, toxoplasmic retinochoroiditis is the commonest form of posterior uveitis in many countries. Correlation of parasite genotype with disease is an important area of new research. Ocular infection with T. gondii often follows ingestion of bradyzoites in undercooked infected meat. Oocysts may survive for an extended period in the environment, and water contaminated with oocysts is an important source in toxoplasmosis epidemics. Ocular toxoplasmosis is preventable by a combination of community activities and personal measures. Public health action is well justified by the considerable burden of congenital and postnatal infections.